Historical perspective of the importance of dental societies - Samplonius Angobaldo, Anton (2022)
This editorial provides a historical review regarding the trade association as one of the most relevant elements of modern dental practice and supports the importance of contemporary dental schools in the development and advancement of the dental profession. The term union is defined as a group of people who have the same trade or profession and associate to order it, defend it, and share experiences. This word involves all the individuals who work in the same professional branch, which contrasts with the concept of union, which implies a voluntary meeting of a group of these.